Application of Geophysical Methods in the Identification of Mineralized Structures and Ranking of Areas for Drilling as Exemplified by Alto Guaporé Orogenic Gold Province - Echague, Jorge; Leão-Santos, Marcelo; Melo, Rodrigo [UNESP]; Mendes, Thiago; Borges, Welitom (MDPI, 2024)
Mineral exploration works conducted in the Alto Guaporé Gold Province (AGGP), situated in the southwest region of the Amazon Craton in Brazil, faces the challenges of many gold provinces around the world, i.e., declines in the discoveries of new economic deposits and increases in exploration costs. Ground geophysical methods, combined with structural analyses and geological mapping, are valuable tools that have potential to improve accuracy in selecting exploration targets and in determining drilling locations. AGGP deposits are primarily associated with regional N20°–W50° inverse faulting and sheared geologic contacts between Meso-Neoproterozoic siliciclastic metasedimentary rocks and Mesoproterozoic basement (granite and volcano–sedimentary sequences). Mining currently occurring in the central portion of the province drives exploration works towards the many existing targets at the area. Among them, the ABP target is one of the most promising for being located few kilometers north of the Pau-a-Pique mine. At the ABP target, gold is associated with hydrothermal alteration located in the sheared contacts and in the hinge zone of folded metasedimentary sequence. Hydrothermal phases include Fe-oxides, sulfide (py), muscovite and quartz veins. In this study, we use magnetic and geoelectric (induced polarization) surveys coupled with structural and geological mapping to identify potential footprints within the ABP target. The results from induced polarization (IP) profiles successfully mapped the shape and orientation of the main structures down to approximately 350 m at the ABP target, indicating potential locations for hydrothermal alteration hosting gold. Additionally, 3D magnetic data inversions illustrated the distribution of magnetic susceptibilities and magnetization vectors associated with shear zone structures and isolated magnetic bodies. Magnetic data highlighted fault zones along the contacts between metamorphic rocks and granites, while IP data identified areas with high chargeability, correlating with sulfidation zones mineralized with gold. These findings suggest a metallogenic model where gold deposits are transported through deep structures connected to regional faults, implying significant tectonic and structural control over gold deposition. The results underscore the potential of multiparameter geophysics in identifying and characterizing deposits in both deep and strike, thereby advancing our understanding of mineral occurrences in the region and enhancing the search for new mineralized zones.
Keywords: Alto Guaporé Gold Province (AGGP); fault zones; geological-geophysical prospecting model; gold exploration; induced polarization (IP); magnetometry